The Hemoglobin Levels in Third Trimester Pregnant Women and Body Weight of Newborn - Yusrawati Hasibuan (Health Notions, 2020)
Hemoglobin level is a biochemical indicator that can be used to determine the nutritional status of pregnant women. The World Health Organization (WHO) recommends that the ideal hemoglobin level for pregnant women is >11 g/dl and is not less than 10.5 g/dl in the third trimester of the pregnancy. High and low levels of hemoglobin during pregnancy affect the weight of the baby because it can disrupt fetal growth in the womb. In Indonesia, MMR is still high, amounting to 305 / 100,000 lives birth. In 2017, from 34 provinces in Indonesia, North Sumatra, including 6 provinces with high MMR. In 2017 MMR in North Sumatra amounted to 58.18 / 100,000 lives birth, while in 2018 MMR increased by 62.18 / 100,000 lives birth. Reports from various research study centers showed that the majority of maternal mortality occurs in high-risk groups. The prevalence of anemia in pregnant women in North Sumatra was 70%. This study aims to determine the relationship between hemoglobin levels of pregnant women in the third trimester with birth weight through literature reviews and articles published in indexed national. This study reviewed 18 articles. Of the 18 articles, 12 of them had the same goal, discussing the relationship between hemoglobin levels of pregnant women in the third trimester of newborn body weight, while 6 other journals discussed different matters. Keywords: hemoglobin levels; pregnant women; baby weight